IDENTIFICATION OF FISH TYPES (LOCAL, NATIONAL AND SCIENTIFIC NAME) RESULT OF FISHERIES (HTU) FISHERIES AND CLASSIFICATION OF FISHING TOOLS IN BANGKA ISLAND, BANGKA BELITUNG - salim, Kurniawan; Rita, Asmarita; Supratman, Okto (Akuatik: Jurnal Sumberdaya Perairan, 2019)
Identification of fish species has an important meaning when viewed from a scientific angle because the entire sequence of subsequent work depends on the results of the correct identification of a species. The purpose of this research is to analyze the types (local, national, scientific name) and types of fishing equipment operating in the Bangka Island. This research was conducted in October 2018 to April 2019 at the Bangka Island. The method was used  purposive sampling. The analysis was carried out by descriptive analysis and PSR (Pressure, State, Response). The result show that there were 30 types of fishing gear that were included in seven classes that are surrounding nets, trawls, seine nets, lift nets, gillnets, traps, hooks and lines. The main fish caught from 30 types of fishing gear used are 73 species which are included in small pelagic fish, large pelagic fish and demersal fish consisting of 38 families. More than 50% of the local names of fish on Bangka Island are different from the names of national fish including Yellow Stalk Fish, in the Bangka area called the Ciu Fish (Selaroides leptolepis), local name Selar Como Fish called Hapau Fish (Atule mate), local name Tetengkek Fish is called Singkur Fish (Megalaspis cordyla), local name Kuwe Onion Trevally Fish is called Sweet Beautiful Fish (Carangoides caeruleopinnatus), Tembang Fish is the local name Tamban Fish (Sardinella gibbosa), Bloso Fish is the local name Buto Cin Fish (Saurida tumbil). Recommendations given are that stakeholders should pay attention to local name so there is no error in data collection and use of enviromentally friendly fishing gear by taking into account the selectivity of fishing gear.